1993
DOI: 10.1073/pnas.90.4.1194
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the complexation of substituted benzenes by a cyclophane host in water.

Abstract: Monte Carlo statistical mechanics simulations have been used to study the complexation of disubstituted benzenes by Diederich's octamethoxy tetraoxaparacyclophane host. Relative free energies of binding were obtained in water at 250C for benzene, p-xylene, p-cresol, p-dicyanobenzene, and hydroquinone from statistical perturbation theory. The computed results agree well with experimental data, including the binding affinity of benzene, which was determined after the calculations were completed. The computed str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Furthermore, freedom of rotation about these bonds (which can readily occur while the guest remains in the cavity) would be favorable in terms of the entropy of the complex. Finally, as noted above, computational studies have suggested that interactions between the methoxy methyl groups of the host and the π-systems of certain guests are stabilizing . Similar stabilizing interactions can also be envisaged between bound guests and the inward-directed OCH 2 groups of B and C.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Furthermore, freedom of rotation about these bonds (which can readily occur while the guest remains in the cavity) would be favorable in terms of the entropy of the complex. Finally, as noted above, computational studies have suggested that interactions between the methoxy methyl groups of the host and the π-systems of certain guests are stabilizing . Similar stabilizing interactions can also be envisaged between bound guests and the inward-directed OCH 2 groups of B and C.…”
Section: Discussionmentioning
confidence: 72%
“…In molecular dynamics studies with cyclophane 3 , it was found that benzene preferred an orientation in which it was not deeply buried in the host cavity . Rather, the benzene ring is “clasped by the four methoxy methyl groups on one side of the host”, an interaction that is energetically favorable due to the partial positive charges on the methyl group hydrogens and the partial negative charges on the aromatic carbons . A similar kind of arrangement can be envisaged for 6 and 7 , wherein the unsubstituted ring of the guest interacts preferentially with the methoxy methyl groups on one side of the host, while the ring bearing the methyl group is inserted in the host cavity, interacting favorably with the host aromatic rings.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Computer simulations have been successfully applied to investigate host−guest recognition processes in solution . By carefully sampling the interactions among host, guest, and solvent, structural arrangements and energetic components which determine experimental binding affinities have been elucidated . The binding of anions by calix[4]pyrrole 1 is explored here in a similar manner and complements a recent study of anion binding by a bis(phenylurea) calix[4]arene derivative .…”
Section: Introductionmentioning
confidence: 99%